Diagnosis of artificial hypoglycemia due to oral hypoglycemic drugs by high-performance liquid chromatography with tandem mass spectrometric detection - M. Y. Yukina; E. A. Troshina; N. F. Nuralieva; V. A. Ioutsi; O. Y. Rebrova; G. A. Mel’nichenko; N. G. Mokrysheva (Сахарный диабет, 2024)
BACKGROUND: Artificial hypoglycemia (ArH) is a decrease of blood glucose levels less than 3 mmol/l due to the deliberate use of hypoglycemic drugs by a patient outside of medical appointments. Timely diagnosis of this kind of hypoglycemia avoids unnecessary numerous examinations and hospitalizations. However, the detection of ArH still remains an extremely difficult task for both the healthcare facility and the attending physician. The foreign literature describes cases of successful detection of deliberate intake of oral hypoglycemic drugs (OHD) using high-performance liquid chromatography with tandem mass spectrometric detection (HPLC-MS/MS). Thus, it is relevant to develop and validate a method for determining OHD using HPLC-MS/MS.AIM: To optimize the diagnosis of ArH due to the use of OHD.MATERIALS AND METHODS: A total of 92 patients were examined. The development of the HPLC-MS/MS method for the detection of the studied OHD (sOHD; n=1-glibenclamide, n=1-gliquidone, n=1-gliclazide, n=1-glimepiride, n=1-glipizide, n=1-nateglinide and n=1-repaglinide) in the blood was carried out in a group of patients with diabetes mellitus type 2 (n=7) who received sOHD, and a group of conditionally healthy people who did not receive any medications (n= 7). To validate the method, the determination of sOHD substances was carried out on groups of patients with hyperinsulinemic nondiabetic hypoglycemia (NDH) of unknown origin (n=11) and with insulinoma (n=67).RESULTS: In the study of blood samples by HPLC-MS/MS in the group of patients with diabetes mellitus type 2, was confirmed in 100% of the cases the use of the drug that the patient received, in the group of conditionally healthy — sOHD were not detected. A false positive result was not obtained in any conditionally healthy and in any patient with insulinoma. ArH was diagnosed in 5 out of 11 patients in the group with hyperinsulinemic NDH of unknown origin, the method identified sOHD glibenclamide and gliclazide in the patients’ blood samples. In the remaining 6 patients of this group, examinations were continued and other causes of NDH were diagnosed. The sensitivity of the method was 100% [74%; 100%], specificity — 100% [95%; 100%].CONCLUSION: The HPLC-MS/MS method has high diagnostic accuracy in the detection and identification of sOHD (glibenclamide, gliquidone, gliclazide, glimepiride, glipizide, nateglinide and repaglinide) in blood samples of patients receiving these drugs. Currently, due to the low availability of the method, this study is advisable to use in patients with hyperinsulinemic hypoglycemia with negative results of first-line insulinoma imaging methods (computed tomography with contrast enhancement, ultrasound and magnetic resonance imaging of the abdominal cavity).